The Role of Phlorotannins to Treat Inflammatory Diseases - K. H. I. N. M. Herath; Dineth Pramuditha Nagahawatta; Lei Wang; K. K. Asanka Sanjeewa (Chemistry, 2025)
Phlorotannins, bioactive compounds isolated from brown seaweeds, have garnered significant attention in recent years for their wide-ranging therapeutic properties, particularly their anti-inflammatory effects. Recent studies have identified phlorotannins as potent inhibitors of inflammatory pathways such as NF-κB, MAPK, JAK/STAT3, and NLRP3. Specifically, phlorotannins derived from seaweeds like Ecklonia cava, Ishige okamurae, and Sargassum horneri have been shown to inhibit the gene and protein expression of pro-inflammatory cytokines and other inflammatory mediators in both in vivo and in vitro conditions. Despite these promising findings, no commercial drugs derived from seaweed phlorotannins have yet been developed to treat inflammatory diseases, and reports of clinical trials remain rare, even in the context of functional food applications for chronic inflammatory conditions. To address this knowledge gap, the authors reviewed peer-reviewed research articles published in 2020 or later, focusing on the anti-inflammatory potential of phlorotannins. The insights provided in this review are expected to be valuable for industries such as functional food research groups and others involved in developing anti-inflammatory therapeutics.